'Missing girls' in China and India: trends and policy challenges. Issue 2 (3rd May 2016) - Guo, Zhen; Das Gupta, Monica; Li, Shuzhuo
ABSTRACT: Child sex ratios plateaued in China between the censuses of 2000 and 2010, a major change from decades of sharp rises. In India they rose by 1.4 per cent during the intercensal period 2001–2011, which is a much slower rate of increase than in previous decades, and reported son preference is falling. In both countries, the largest declines are in regions that had the highest child sex ratios earlier, while some surrounding regions show rises. State policies to reduce sex-selection through offering financial incentives or banning the use of sex-selective technology show limited evidence of effectiveness. In China, the overall level of sex-selection remained stable, while the census data show a sharp shift towards sex-selection at the first birth—likely related to the mode of implementation of the program to reduce sex-selection. Studies indicate that media outreach can be very effective at changing norms and behaviors, including reducing son preference. Reducing the demand for sex-selection may offer the most effective long-term solution.